The role of magnetic fields in pre-main sequence stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Hussain, Gaitee A. J.; Alecian, Evelyne
Abstract: Strong, kilo-Gauss, magnetic fields are required to explain a range of observational properties in young, accreting pre-main sequence (PMS) systems. We review the techniques used to detect magnetic fields in PMS stars. Key results from a long running campaign aimed at characterising the large scale magnetic fields in accreting T Tauri stars are presented. Maps of surface magnetic flux in these systems can be used to build 3-D models exploring the role of magnetic fields and the efficiency with which magnetic fields can channel accretion from circumstellar disks on to young stars. Long-term variability in T Tauri star magnetic fields strongly point to a dynamo origin of the magnetic fields. Studies are underway to quantify how changes in magnetic fields affect their accretion properties. We also present the first results from a new programme that investigates the evolution of magnetic fields in intermediate mass (1.5–3M⊙ ) pre-main sequence stars as they evolve from being convective T Tauri stars to fully radiative Herbig AeBe stars.